SURFACE CHARGE CONCENTRATIONS ON SILICA IN DIFFERENT 1.0 M METAL-CHLORIDE BACKGROUND ELECTROLYTES AND IMPLICATIONS FOR DISSOLUTION RATES - Karlsson M.; Craven C.; Dove P.M.; Casey W.H. (My University, 2001)
The empirical rate laws formulated to describe the dissolution rates of oxide minerals include the surface charge concentration that results from the protonation and deprotonation of surface functional groups. Previous experiments on quartz and silica have shown that dissolution rates vary as a function of different background electrolyte solutions, however, such experiments are often conducted at elevated temperatures where it is difficult to estimate surface charge along with the dissolution rates. In the present study we measure surface charge concentrations for silica in different electrolyte solutions at 298 K in order to quantify the extent to which the different counterions could affect the dissolution rates through their influence on the surface charge concentrations. The experimental solutions in the electrolyte series: LiCl, NaCl, KCl, RbCl, CaCl2, SrCl2 and BaCl2 were prepared to maintain a constant metal concentration of 1.0 M. For the alkali-metal chlorides, the surface charge concentrations correlate with the size of the hydrated alkali metal, consistent with the idea that these counterions affect charge via outer-sphere coordination that shield proton surface complexes from one another. The reactivity trend for alkaline-earth cations is less clear, but the data demonstrate distinct differences in the acid-base properties of the silica surface in these different electrolytes. We then discuss how these trends are manifested in the rate equations used to interpret dissolution experiments.
Keywords: OXIDE SURFACE CHEMISTRY; DISSOLUTION KINETICS; SILICA